IMPLEMENTASI KEGIATAN MEMBACA PERMULAAN PADA SISWA KELAS I SD MELALUI PROGRAM KKN DI UPT SD NO.78 BALANG - Zainuddin, Siti; Syafiqah , Nabila Rana; Firdaus , Andi Mulawakkang; Ratnawati (Almeera Education, 2025)
Early reading activities are the foundation for mastering language skills in elementary schools. This study aims to describe the implementation of early reading activities in first-grade students of SDN 78 Balang and analyze the supporting and inhibiting factors of its implementation. The method used is descriptive qualitative research with teachers and first-grade students as subjects. Data were collected through observation, interviews, and documentation. The results show that 75% of students have recognized vowels and consonants, but 30% still have difficulty reading independently, only being able to read when spelled. Supporting factors include the involvement of KKN students, teacher support, and the motivation of some students. Inhibiting factors are differences in ability, low motivation of some students, and minimal parental involvement. Practical implications, more personalized learning strategies and increased communication between schools and parents are needed to improve students' early reading outcomes..